Development of e-book on video integration on seaweed processing materials in vocational education - Yulda; Puspitasari, Diana; Prasetiyo, Himawan; Rudi, Mad (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Seaweed in Indonesia in 2023 reached a significant figure of up to 9 million tons. The utilization of seaweed products encompasses various industrial sectors, both food and non-food. In the process of seaweed processing, the role of education becomes one of the important roles to enhance students’ understanding of its potential and processing. This study aims to describe the stages of developing e-book-based learning media integrated with video and to measure the improvement in students’ understanding of the media. This research uses the 3D development model (Define, Design, Develop) with an approach that includes the stages of planning, creation, and validation testing. Validation data were collected using a Likert scale for content experts and media experts, while for users, a pretest-posttest was used. Based on the validation results by the three expert team members, the research findings indicate that the content expert validation is 93% (Very Feasible), and the media expert validation is 85.3% (Very Feasible). Additionally, the N gain from the pretest posttest results, which measures the users’ understanding level, is 0.4 (Moderately High). In addition, it was found that the average response of students to the media trial was 63.47% (Interesting). Based on the results of this study, it shows that the E-book media integrated with video can significantly enhance students’ understanding, while also providing an interesting and interactive learning alternative. Therefore, it can be stated that the learning media using video-integrated e-books for seaweed processing materials is capable of attracting students’ attention and interest in learning.